2020
DOI: 10.3390/pr8040384
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Landfill Leachate Treatment by Microalgae: Current Status and Future Directions

Abstract: Solid waste generation has been projected to increase worldwide. Presently, the most applied methodology to dispose of solid waste is landfilling. However, these landfill sites, over time release a significant quantity of leachate, which can pose serious environmental issues, including contamination of water resources. There exist many physicochemical and biological landfill leachate treatment schemes with varying degrees of success. With an increasing focus on sustainability, there has been a demand for devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 51 publications
1
19
0
2
Order By: Relevance
“…The sample also contained a high content of TDS with value of 10,800 mg/L. The concentrations of raw leachate were found within reported range and suggested that analyzed leachate are at intermediate stage, between acidogenic and matured (methanogenic) phase of biodegradation [ 3 , 39 42 ].…”
Section: Resultsmentioning
confidence: 78%
“…The sample also contained a high content of TDS with value of 10,800 mg/L. The concentrations of raw leachate were found within reported range and suggested that analyzed leachate are at intermediate stage, between acidogenic and matured (methanogenic) phase of biodegradation [ 3 , 39 42 ].…”
Section: Resultsmentioning
confidence: 78%
“…In these open-air garbage dumps, the solid wastes can be dispersed and degraded by abiotic and biotic factors, producing a gamma of solid, gaseous, and liquid products; the latter is known as leachate. This wastewater flows out from a landfill or an open-air garbage dump sites due to precipitation, ground-water intrusion, moisture content of waste, and rate of evaporation [18]. The volume and pollutant composition of this leachate wastewater fluctuate over time; therefore, in the early acid phase, there exists a high concentration of the four groups of pollutants (dissolved organic matter, heavy metals, inorganic macrocomponents, and xenobiotic organic compounds); finally, in the long methanogenic phase, the leachate liquid has a lower concentration of the four groups of pollutants and is characterized by its very low concentration of heavy metals and biochemical oxygen demand/chemical oxygen demand (BOD/COD) ratio [19][20][21].…”
Section: Use Of Native Microalgae For Pollutants Removal 21 Leachate ...mentioning
confidence: 99%
“…However, in some cases, the amount of water required would make the process unsustainable and barely possible. According to the review by Nawaz et al [56], freshwater consumption is one of the major drawbacks of the LL phycoremediation process as it increases material costs and water footprint. To address this issue, several studies have investigated the basic idea of utilizing an LL-wastewater mixture as the medium for microalgal growth.…”
Section: Possible Optimizations Of the Phycoremediation Processmentioning
confidence: 99%
“…was observed to accumulate high lipid (20%) and carbohydrate (41%) content. Nawaz et al [56] also suggested that phosphorus deficiency typical to LL may be remedied by diluting the LL with agricultural effluent rich in phosphorus.…”
Section: Possible Optimizations Of the Phycoremediation Processmentioning
confidence: 99%